Perspektif Orang Tua pada Kesehatan Gigi Anak Usia Sekolah - Aisyah Nurjanah; Rafi Farizki; Agus Rohmat Hidayat; Nur Saebah (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2021)
Abstract – Dental health is a component of health in school-age children that their parents need to pay attention to. The subjects in this study consisted of 50 parents who had school-age children between 4-10 years in Harjamukti District, Cirebon City. The aim of this research was to look at the parents' perspective on the dental health of school-age children. The method used is observational through a questionnaire on parents who have school-age children. Data collection was carried out through interviews and questionnaires. The results of the study show that most parents have a fairly good perspective and are concerned about the dental health of their children who are at school age. However, there are also some parents who do not understand the dangers of dental caries in children. In this case, parents with a fairly good perspective and care about children's dental health have no relationship with the parents' occupational factors.